2017
DOI: 10.1111/bcp.13430
|View full text |Cite
|
Sign up to set email alerts
|

Global population pharmacokinetics of the investigational Aurora A kinase inhibitor alisertib in cancer patients: rationale for lower dosage in Asia

Abstract: AimsThis population pharmacokinetic analysis was conducted to describe quantitatively the regional differences and sources of interpatient variability on the apparent oral clearance of alisertib.MethodsA population pharmacokinetic analysis was performed on data from 671 cancer patients in Western countries and in Japan/East Asia to whom alisertib 5–150 mg once or twice daily (b.i.d.) was administered in multiple dosing schedules. The final model was used to simulate alisertib pharmacokinetics in patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
(57 reference statements)
2
20
0
Order By: Relevance
“…In vitro studies indicated that UDP‐glucuronosyltransferase (UGT) 1A8, 1A3, and 1A1 were the UGT isoforms responsible for the formation of alisertib acyl glucuronide metabolite M1 (Takeda data on file). Although the relative contributions of these individual UGTs to overall alisertib glucuronidation has not been determined, it has been established that UGT1A1 is not a major contributor based on population pharmacokinetic analyses in which patients harboring the UGT1A1*28 allele did not have reduced apparent clearance of alisertib . There was a notable increase in systemic exposures of M1 in patients with moderate or severe hepatic impairment (approximately 6‐ to 10‐fold greater metabolite/parent AUC ratio vs normal hepatic function), possibly explained by a reduction of its biliary excretion because of impaired hepatic function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro studies indicated that UDP‐glucuronosyltransferase (UGT) 1A8, 1A3, and 1A1 were the UGT isoforms responsible for the formation of alisertib acyl glucuronide metabolite M1 (Takeda data on file). Although the relative contributions of these individual UGTs to overall alisertib glucuronidation has not been determined, it has been established that UGT1A1 is not a major contributor based on population pharmacokinetic analyses in which patients harboring the UGT1A1*28 allele did not have reduced apparent clearance of alisertib . There was a notable increase in systemic exposures of M1 in patients with moderate or severe hepatic impairment (approximately 6‐ to 10‐fold greater metabolite/parent AUC ratio vs normal hepatic function), possibly explained by a reduction of its biliary excretion because of impaired hepatic function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relative contributions of these individual UGTs to overall alisertib glucuronidation has not been determined, it has been established that UGT1A1 is not a major contributor based on population pharmacokinetic analyses in which patients harboring the UGT1A1*28 allele did not have reduced apparent clearance of alisertib. 5,15 There was a notable increase in systemic exposures of M1 in patients with moderate or severe hepatic impairment (approximately 6-to 10-fold greater metabolite/parent AUC ratio vs normal hepatic function), possibly explained by a reduction of its biliary excretion because of impaired hepatic function. The magnitude of relative increase in systemic exposure of the active oxidative metabolite (M2) did not meaningfully differ from that observed for the parent drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations